Adolescents in acute mental health crisis—Pilot-evaluation of a low-threshold program for emotional stabilization - Dixius, Andrea; Michael, Tanja; Altpeter, Adriana; Ramos Garcia, René; Möhler, Eva (Frontiers in Child and Adolescent Psychiatry, 2023)
Background: Referrals for child and adolescent acute psychiatric treatment have spiked in the last two years.To provide these adolescents with a fast-acting intervention, a novel treatment approach for acute emotional dysregulation was evaluated in this study.Methods: 156 adolescents between the age of 13-18 years who were admitted to a psychiatric unit for acute emotional or behavioral dysregulation participated in a 5-week-group program (Stress-Arousal-Regulation-Treatment, START) which consisted of two sessions per week (60 min/session). Pre-and post intervention psychometric measures were derived for each participant applying the Self-Control Scale (SCS-13), the FEEL-KJ capturing adaptive and maladaptive emotion regulation strategies, the Perceived Stress Scale (PSS-10), as well as the Strengths and Difficulties Questionnaire (SDQ).The mean score of maladaptive emotion regulation strategies of the FEEL-KJ significantly decreased post treatment (d=-0.24, p=.001), while there was an increase in adaptive emotion regulation strategies (d=0.25, p=.001). The post-intervention-assessment revealed significantly lower scores in the PSS-10 (d=-0.34, p<.001), as well as SDQ mental health problems (d= -0.17, p=.018) and disorders (d=-0.15, p=.015). The Self-Control Score increased significantly after the intervention (d=0.21, p=.001).In this large sample, the low-threshold intervention START significantly improved emotion regulation and self-control and reduced perceived stress as well as several scales of the strengths and difficulties questionnaire, pointing to a good feasibility and indicating efficiency to provide support to adolescents with acute mental health problems when applying this short-term treatment.